Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.14400/jdc.2016.14.3.391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Verbal Abuse Experience, Coping Style and Resilience on Emotional Response and Stress During Clinical Practicum among Nursing Students

Abstract: This study aimed to investigate the effect of verbal abuse experience, coping style and resilience on emotional response and practical stress. 261 nursing students participated in this study. The Data were collected using self-report questionnaires from Dec. 1 to Dec. 20, 2014. We found a positive correlation among verbal abuse experience, emotional coping style and stress during clinical practicum; a positive correlation among problem coping style, emotional coping style and resilience; a positive correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…They experienced violence in emergency rooms, general wards, psychiatric wards, and intensive care units; as many as 40% to 98.2% of study respondents experienced violence [6,[15][16][17][18]. Nursing students experiencing verbal abuse or physical violence complained of psychological problems, such as anxiety, fear, decreased self-confidence, anger, and hostility, as well as physical problems caused by trauma; some of them even wanted to quit their nursing program [6,[18][19][20][21][22]. Many used passive emotion-focused coping styles of neglect or avoidance instead of asking for help or reporting violence [17,[22][23][24].…”
Section: Need For Studymentioning
confidence: 99%
“…They experienced violence in emergency rooms, general wards, psychiatric wards, and intensive care units; as many as 40% to 98.2% of study respondents experienced violence [6,[15][16][17][18]. Nursing students experiencing verbal abuse or physical violence complained of psychological problems, such as anxiety, fear, decreased self-confidence, anger, and hostility, as well as physical problems caused by trauma; some of them even wanted to quit their nursing program [6,[18][19][20][21][22]. Many used passive emotion-focused coping styles of neglect or avoidance instead of asking for help or reporting violence [17,[22][23][24].…”
Section: Need For Studymentioning
confidence: 99%
“…Today, the developmental tasks experienced by university students have become more wide ranged and diverse, resulting in larger amounts of stress; consequently, resilience is a critical factor in enabling university students to better manage their lives . Jeong and Lee examined nursing university students and found that higher resilience leads to more developed response mechanisms. Kim indicated that university students with higher resilience have higher adaptive abilities, and the positive tendency component of resilience was found to influence the ability to control future uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a statistically signifcant positive correlation was found among nursing students' levels of resilience, care behaviors, and violence management competencies (Table 6). When the literature is examined, Jeong and Lee [79] reported a positive relationship between verbal abuse experience and emotional coping style in their study to determine the efect of verbal abuse experience, coping style, and resilience on emotional response and stress in nursing students during clinical practice. Karabey et al [55], in their study to determine the refection of nursing students' violence tendencies on care behaviors, found that there was a statistically negative relationship between students' violence tendencies and care behaviors.…”
Section: Discussionmentioning
confidence: 99%